Formation of single carbon chain bridging two SWCNTs via tensile deformation of nanobud junction. (5th May 2016) - Yang, Xueming; Huang, Yanhui; Wang, Longjie; Cao, Bingyang; To, Albert C.
Abstract: Molecular junctions formed by a single carbon chain (SCC) bridging two SWCNTs are highly desirable for molecular electronic nanodevices; however, the fabrication is still quite challenging. In this study, we present a novel method to produce a SCC bridging the outer wall of two SWNTs. By separating the carbon nanotube embedding nanobuds junction, carbon atom chain including a few tens of atoms or even up to 100 carbon atoms bridging two SWNTs can be formed. Moreover, we find that embedding nanobuds junction shows extraordinary room temperature superplasticity. The laddering effect, in which the atom chain can be continuously pulled out from the fullerene molecule in the nanobuds junction under tensile loading, is exhibited in this work. Graphical abstract: Highlights: A novel computational method is presented to produce a single carbon chain bridging between two single wall carbon nanotubes. Embedding nanobud junctions show extraordinary room temperature superplasticity with up to 573.6% elongation to failure. The obtained single carbon atom chains show good thermal stability up to 2000 K.